Rajchman and the League of Nations' Health Intervention in Greece - Andersson, Rasmus Wasim (Culture and History: Student Research Papers, 2023)
This article offers insights into the development and implementation strategies of the League's health intervention in Greece. The first part uses Ludwik Rajchman, medical director of the League of Nations, as an analytical prism. It explores his active involvement, how he drew on a mainstream approach to social hygiene and how he recruited expertise globally. It is also argues that Rajchman likely drew inspiration from Australian hospital systems, which he studied in preparation for the intervention. The second part highlights the deliberate emphasis on technical aspects of the intervention for diplomatic reasons. Seeking funding from the Rockefeller Foundation, Rajchman aimed to portray the intervention as a technical rather than political endeavor. Moreover, emphasizing the technical nature of Rajchman's team allowed for presenting its efforts as noninvasive with respect to Greek sovereignty, positioning the intervention as a continuation of Greek government initiatives.